DIGITAL LITERATION PROFICIENCY OF ELEMENTARY SCHOOL STUDENTS IN THE ERA OF THE INDUSTRIAL REVOLUTION 4.0 - Hadiansah, Dede; Setiawardani, Wawan; Sholeh, Muhammad (PrimaryEdu : Journal of Primary Education, 2021)
Students at the age of primary education are faced with a challenge in using digital technology, namely (a) the ability to sort information that is suitable for use and follow; (b) addiction to digital technology and the internet; and (c) changes in behavior and character. The purpose of this study is to identify: (a) obtaining information from digital media by elementary school students; (b) the use of information from digital media by elementary school students using; (c) the challenges faced by elementary school students in obtaining information using digital media; (d) the expectations of elementary school students regarding learning using digital media. The research method used is the phenomenological research method. The results of the research, some students use digital literacy only to find information. Meanwhile, a few elementary students have carried out the learning process in the form of products from the use of digital literacy. Digital literacy can be a suitable learning medium in the era of the industrial revolution 4.0, but its use must be monitored and limited.